Analysis of Alpina officinarum Hance, chemically and biologically - Fatemah A. Alasmary; Eman A. Assirey; Reham M. El-Meligy; Amani S. Awaad; Lara A. El-sawaf; Menatallah M. Allah; Saleh I. Alqasoumi (Elsevier, 2019)
Alpinia officinarum Hance is one of the most commonly used herbs belongs to Family Zingiberaceae. The current work deals with the qualitative and quantitative chemical study of this plant rhizomes in addition to the investigation of its anticancer activities. The results of the qualitative analysis showed a variation of phytochemical contents in this plant. While quantitative analysis showed a very promising percentage of active materials and Pharmacopeial constants. Analysis of elements like Cu, Zn & Mg were variable chromium was the lowest (0.680 ppm). The active constituents showed the highest percentage of carbohydrate (20.25 ± 1.11) and the lowest was of lipid (2.79 ± 1.03), other constituents percentage ranged from 5.11 ± 1.31 to 18.26 ± 1.24 for protein and flavonoids respectively. The pharmacopeial constant determinations reported the highest in moisture content (11.02 ± 1.05), Total ash, water-soluble ash, and acid insoluble ash were varied in values (5.64 ± 1.31 to 2.01 ± 1.12).The evaluation of the antitumor activities (in vitro) of the investigated plant rhizomes extract showed that; it exhibited a direct cytotoxic effect on the growth of some cell lines compared to the standard drug vinblastine sulphate. The activities were recorded against two cell lines; A-549 (Lung carcinoma) and CACO (colorectal carcinoma) with IC50 6.72 ± 0.5 and 7.6 ± 0.3 µg/ml respectively, these effects were better than the standard drug vinblastine sulphate (IC50 were 24.6 ± 0.7& 30.3 ± 1.4 µg/ml). Moreover, the effect of the investigated extract was also promising on the other three cell lines (HCT-116 (Colon carcinoma, Hela (Cervical carcinoma) & Pc3 (prostate cancer) the best effect was on Hela with IC50 of 24.5 ± 1.1 µg/ml better than vinblastine sulphate (59.7 ± 2.1 µg/ml). Keywords: Cell lines, Anticancer effect, Pharmacopeia constant, Phenolic compounds, Flavonoids, Tannins, Liver and kidney functions